Borehole electrokinetic responses in fracture dominated hydraulically conductive zones - Hunt, C; Worthington, M (2000)
Electrokinetic borehole logging experiments conducted in fracture dominated Devonian metasediments and Carboniferous limestone boreholes containing dissolution discontinuities, indicate a strong relative amplitude correlation between a downhole electrokinetic response and previously obtained hydrogeological data for the respective boreholes. Voltages in the range 0.2-1.5 volt were recorded per MPa of gauge pressure induced in the borehole fluid. A relationship between fracture aperture and the frequency content of the electrical data has also been observed.